2022
DOI: 10.1002/ana.26382
|View full text |Cite
|
Sign up to set email alerts
|

Menopause Status Moderates Sex Differences in Tau Burden: A Framingham PET Study

Abstract: Objective: Women have a higher lifetime risk of Alzheimer's disease (AD) than men. Among cognitively normal (CN) older adults, women exhibit elevated tau positron emission tomography (PET) signal compared with men. We explored whether menopause exacerbates sex differences in tau deposition in middle-aged adults. Methods: 328 CN participants from the Framingham Study (mean age = 57 years (AE10 years), 161 women, of whom, 104 were post-menopausal) underwent tau and β-amyloid (Aβ)-PET neuroimaging. We examined gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 56 publications
5
46
0
Order By: Relevance
“…We focused on temporal, parietal, and occipital brain regions that have shown sex differences on tau PET in female individuals compared with males. 3,28…”
mentioning
confidence: 99%
“…We focused on temporal, parietal, and occipital brain regions that have shown sex differences on tau PET in female individuals compared with males. 3,28…”
mentioning
confidence: 99%
“…In addition, recovery in aspects of brain structure and metabolism postmenopause were linked to better postmenopause global cognition [28 ▪▪ ]. In a separate study, Buckley and colleagues showed in a sample of 328 cognitively normal individuals at midlife (mean age = 57), that postmenopausal, but not premenopausal women had greater levels of tau protein than men, as assessed by tau-Positron Emission Tomography [30 ▪▪ ].…”
Section: Risk Factors For Poor Cognitive Aging In Womenmentioning
confidence: 99%
“…As with work on menopause-related risks for cognitive decline, there are discrepancies among human clinical trials vs. observational studies of MHT on cognitive outcomes, as well as differences when comparing human and animal model literature, regarding what genetic and medical risks might define women who benefit most from MHT, what treatment should be given, and for how long [29,30 ▪▪ ,31]. Regarding who to treat, age, APOE ε4 status, and medical and lifestyle risks [29] are important to consider.…”
Section: Interventions To Support Brain Health In Womenmentioning
confidence: 99%
“…Area 35, corresponding to the transentorhinal region and medial perirhinal cortex 24,41 , has thus far received little attention in regards to endogenous ovarian hormone uctuations. This constitutes a critical knowledge gap given the relevance of this subregion to dementia progression and that changes in hormone status have been proposed to underlie sex differences in Alzheimer's disease pathology [42][43][44] .…”
Section: Introductionmentioning
confidence: 99%